2014
DOI: 10.1002/jaba.152
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of interactive computer training to teach instructors to implement discrete trials with children with autism

Abstract: Discrete-trial instruction (DTI) is a teaching strategy that is often incorporated into early intensive behavioral interventions for children with autism. Researchers have investigated time- and cost-effective methods to train staff to implement DTI, including self-instruction manuals, video modeling, and interactive computer training (ICT). ICT combines the best components of self-instruction manuals and video models, and have the same benefits; however, there is limited research on this training method. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 25 publications
5
70
1
8
Order By: Relevance
“…In sum, both BST and CBI have previously been demonstrated to be effective for training staff in many different skills, including the implementation of DTT (e.g., Pollard et al, ; Sarokoff & Sturmey, ; Serna et al, ; Ward‐Horner & Sturmey, ). This study extended Nosik et al () by offering an additional comparison of CBI to BST with an evaluation of the return on investment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In sum, both BST and CBI have previously been demonstrated to be effective for training staff in many different skills, including the implementation of DTT (e.g., Pollard et al, ; Sarokoff & Sturmey, ; Serna et al, ; Ward‐Horner & Sturmey, ). This study extended Nosik et al () by offering an additional comparison of CBI to BST with an evaluation of the return on investment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, participants trained with BST reported feeling very competent to perform the task, whereas CBI-trained participants reported feeling somewhat competent. These studies and others (Higbee et al, 2016;Pollard et al, 2014;Serna et al, 2016) illustrate the utility of interactive CBI programs (e.g., video clips, instructions, quizzes) to train people to implement various components of DTT.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…However, only the paper by Pollard and associates [17] are actually employed computer based learning whereas the other discrete trial studies involved videos, instructional guides or onsite training. In a research paper, following her dissertation, Pollard et al [17] reported an evaluation of interactive computer training to teach instructors to implement discrete trials with children with autism. Researchers have investigated time-and cost-effective methods to train staff to implement DTI, including self-instruction manuals, video modeling, and interactive computer training (ICT).…”
Section: E-learning Articles Focusing On Discrete Trial Trainingmentioning
confidence: 99%
“…Training As another form of e-learning, telehealth, adopts the communication technologies to deliver specific services over a certain geographical distance Dudding [16] and Turner [17]. It is accessible anytime and anywhere using basic reasonablypriced equipment, and it boasts off some interactive, tailormade features to relay and exchange information [18].…”
Section: B Studies Applying Telehealth Approaches In E-learningmentioning
confidence: 99%